Clinical study of analgesia in brachytherapy for cervical cancer - Mei Liu; Hai‐Yan Wu; Jian Li; Meng‐Yu Ou; Shu‐Fang Sun; Ying Tang; Xiu‐Juan Zhao (Precision Radiation Oncology, 2023)
Abstract Objective This study investigated the analgesic effects in patients with cervical cancer during brachytherapy. Methods In this prospective study, 100 patients with cervical cancer who were admitted to Chongqing University Cancer Hospital between July 2021 and April 2022 were randomly divided into an analgesia group (n = 50) and a control group (n = 50). The visual analog scale (VAS) scores at applicator placement‐T1, CT‐scan‐T2, and removal ‐T3, self‐rating anxiety scale (SAS) and self‐rating depression scale (SDS) scores before brachytherapy, short‐term clinical efficacy, and patient satisfaction were compared between the two groups. Results The VAS score of the analgesia group was significantly different at T1 (0 vs. 4.34±1.02, t = 67.40, p < 0.001), but not in the control group; however, there was no significant difference between the two groups at T2 (t = ‐0.49, p = 0.623) and T3 (t = ‐0.12, p = 0.912). The SAS and SDS scores first decreased and then increased in the analgesic group and increased in the control group with increasing brachytherapy time. Except for the first measurement, the differences between the two groups were statistically significant (all p < 0.001). The application of interstitial implantation (p = 0.027), local efficacy (p = 0.047), and patient satisfaction rates (p = 0.025) were higher in the analgesic group than in the control group. Conclusion Analgesia can relieve pain, maintain physical and mental health, and improve outcomes and patient satisfaction rates for cervical cancer.